RNA interference-aided knockdown of a putative saccharopine dehydrogenase leads to abnormal ecdysis in the brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae). Issue 4 (24th April 2015) - Wan, P.-J.; Yang, L.; Yuan, S.-Y.; Tang, Y.-H.; Fu, Q.; Li, G.-Q.
Abstract: The brown planthopper Nilaparvata lugens is a serious phloem-feeding pest of rice in China. The current study focuses on a saccharopine dehydrogenase (SDH) that catalyzes the penultimate reaction in biosynthesis of the amino acid lysine (Lys), which plays a role in insect growth and carnitine production (as a substrate). The protein, provisionally designated as NlylsSDH [a SDH derived from yeast-like symbiont (YLS) in N. lugens ], had a higher transcript level in abdomens, compared with heads, wings, legs and thoraces, which agrees with YLS distribution in N. lugens . Ingestion of Nlylssdh targeted double-stranded RNA (ds Nlylssdh ) for 5, 10 and 15 days decreased the mRNA abundance in the hoppers by 47, 70 and 31%, respectively, comparing with those ingesting normal or ds egfp diets. Nlylssdh knockdown slightly decreased the body weights, significantly delayed the development of females, and killed approximately 30% of the nymphs. Moreover, some surviving adults showed two apparent phenotypic defects: wing deformation and nymphal cuticles remained on tips of the legs and abdomens. The brachypterours/macropterours and sex ratios (female/male) of the adults on the dsRNA diet were lowered compared with the adults on diets without dsRNA. These results suggest that Nlylssdh encodes a functional SDH protein. The adverse effect of Nlylssdh knockdown on N. lugens implies the importance of Lys in hopper development. This study provides a proof of concept example that Nlylssdh could serve as a possible dsRNA-based pesticide for planthopper control.